ERADICATING SEXUAL VIOLENCE FROM AN EARLY AGE THRU THE SCHOOL-BASED CHILD SELF PROTECTION for SEXUAL ABUSE (C-SPoSA) PROGRAM - JUM NATOSBA (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Sexual violence against children, whether girls or boys, must not be tolerated. Sexual violence against children can occur anywhere and anytime, and can be perpetrated by anyone, whether it is a family member, school staff, or others. Therefore, children need to be equipped with proper knowledge of sexuality so that they can be protected from sexual violence. This activity aims to increase students' knowledge at SD Negeri 79 Praumulih School. Method: This community service activity is carried out in several stages, including preparation, implementation, which involves the implementation of Comprehensive Sexual Violence Prevention Education for children, and evaluation and assessment of the activity results. The School-Based Child Self Protection For Sexual Abuse (C-Sposa) program combines illustrated storybooks, challenge games, the song